Advancing autonomy in Tunisian higher education: Exploring the role of technology in empowering learners - Mimoun Melliti; Mansour Henchiri (Educational Technology Quarterly)
This study explores technology-based learner autonomy in Tunisian higher education, focusing on the Raqqada English department. It examines student engagement with technology-driven learning and the challenges faced by educators, highlighting a gap between students' theoretical readiness for self-directed learning and their actual use of digital tools. Utilising a mixed-methods approach, quantitative data were collected from 102 English students via questionnaires, and qualitative data from interviews with 25 educators. Findings reveal that while 80% of students engage in autonomous learning outside the classroom, in-class technology usage is significantly lower, indicating a disconnect with existing infrastructure. Furthermore, 76% of students acknowledge technology's role in supporting diverse learning styles, and 67% link smart classrooms to increased motivation. However, challenges such as limited digital literacy, inadequate training, and poor infrastructure hinder effective technology integration. Educators expressed concerns about rigid teaching methods and insufficient autonomy at earlier educational levels, suggesting that autonomy is better developed at the master's level. The study concludes that enhancing infrastructure, training, and digital resource availability is crucial for advancing learner autonomy. Recommendations include fostering intercultural collaboration through programs like Collaborative Online International Learning (COIL) and implementing varied assessment methods to evaluate learner autonomy better. Additionally, professional development programs for educators and students are necessary to promote autonomy and active learning strategies.